Development and evaluation of a specific judo grip strength test - Heinisch, H. D.; Knoll, Kl. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
Practical implications and prospects: The new testing device offers opportunities for a differentiated control of the level of performance and can be applied for continuous performance diagnostics in connection with the following research problems: A summary of the international scientific studies indicates that judo players are not stronger than non-judo players in absolute terms (peak grip force), but the judo players had a higher resistance to fatigue (6). So one of our aims is to establish and to evaluate references in grip strength endurance. Investigations about interventions of a specific grip strength training (which training contents and methods are appropriate to increase the grip strength?).